Table of Content - - (Journal of Arabic Language Sciences and Literature, 2023)
Table of Content:1. Disutopian Manifestations in the Algerian Novel: A Case Study "Watan Men Zojaj, A Fragile Homeland"Mrs. Fareda Jmea'an Alkrenawi2. Deconstructive principles of Jacques DerridaCo-Prof. Hanadi Muhammad Behairi3. The Usage: A Historical Analytical StudyDr. Rana Aniss Bleik4. Linguistic Patterns’ Role in Arabic -Chinese TranslationLao Lingling5. The syntactic preferences of Mohieddin Darwish in his book "Explanation and Explanation of the Qur'an"Dr. Jahangir Amiri, Mr. Salah Mohsin Hazim Al-Rawwas , Mr. Mohamed Zaher Abdel Mohsin Al-Anbaki6. The grammatical embed phenomena in The Holy QuranDr. Abdelrahman Mudawi Abdelrahim Alhadi, Mrs. Aysha Mohammed Abdu Allah Alhammadi7. The effect of the morphological structure in determining the function of the grammatical phenomenon and its interpretationDr. Ahmad Hilal Al-Salaymeh8. Al-Dhafiri al-Yamani's position on Ibn Al-Hajib's opinions in his book Al-Manahil AI-Safia to revealing the healing meaningsMrs. Amani Zaid Ali Al-Shalili , Prof. Hadi Abdulla Naji Shamsan
Keywords: Journal of Arabic Language and Literature